(untitled) (Ustozlar uchun, 2026)
Relevance The treatment of the fibrous form of hyperplastic gingivitis presents significant difficulties. The disease progresses due to poor oral hygiene, where soft and hard dental deposits cause constant irritation of the marginal gingiva and its reactive overgrowth. With a prolonged course, the tissues undergo fibrous degeneration. In such cases, removing only the causative factor (plaque) is not sufficient to restore the original gum contour, and surgical correction is required.